2022
DOI: 10.1177/10567879221094302
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Graduate Students’ Experiences in Online International Development and Peace Through Sport Courses Using English-Medium Instruction During the COVID-19 Pandemic

Abstract: The purpose of this study was to investigate five Japanese graduate (master's level) students’ experiences in online courses in international development and peace through sport that used English as the medium of instruction. The study was situated in the framework of andragogy theory and used a descriptive-qualitative design using an in-depth, semistructured interview approach using online oral and written interviews. Three emergent themes were established. These recurrent themes were (a) learning online spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Recently, scholars in sport and physical education have used andragogy theory to study graduate students’ experiences (Sato et al, 2017a) and engagement (Sato & Haegele, 2017) in online courses as well as online course materials and content (Sato et al, 2017b) and graduate professional development (Sato & Haegele, 2018). More recently, andragogy theory has been used to investigate graduate students’ experiences in online SFD courses in an EMP (Oishi et al, 2022). In summary, the results of these studies demonstrated that graduate students believed that the online courses helped them store and access online reading materials and assessment tools that solved academic and social issues and concerns.…”
Section: Theoretical Framework and Purposementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, scholars in sport and physical education have used andragogy theory to study graduate students’ experiences (Sato et al, 2017a) and engagement (Sato & Haegele, 2017) in online courses as well as online course materials and content (Sato et al, 2017b) and graduate professional development (Sato & Haegele, 2018). More recently, andragogy theory has been used to investigate graduate students’ experiences in online SFD courses in an EMP (Oishi et al, 2022). In summary, the results of these studies demonstrated that graduate students believed that the online courses helped them store and access online reading materials and assessment tools that solved academic and social issues and concerns.…”
Section: Theoretical Framework and Purposementioning
confidence: 99%
“…For example, students may have more difficulty participating orally and students may be less engaged in lessons (Querol-Julián, 2023). Oishi et al (2022) found that students in online EMP courses felt anxious and had difficulty maintaining eye contact with others and struggled completing group projects. However, online courses also offer a number of advantages and opportunities; for example, Soruç et al (2018) found that audio recording lectures was an important strategy for graduate students in online courses because virtual learning contexts can support students’ listening comprehension by allowing graduate students to replay the lecture as many times as needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation